Utilizing Geographic Information System as a Tool for Pavement Management System - Hana NAGHAWI; Taqwa ALHADIDI; O. Al KILANY; A. Al SHARIEF (International Journal of Applied Methods in Electronics and Computers, 2016)
Pavement management systems (PMS) have evidenced to become an essential and valuable tool for highway agencies in quantifying the overall pavement maintenance needs and presenting the alternative maintenance plans under budget limitations.  An essential phase of the development of a PMS is to collect, manage and analyse the pavement condition data, containing various structural and functional distresses, in considerably detailed format.  Recently, the infusion of the new spatial technologies such as Geographic Information System- GIS has enhanced the PMS development and implementation efforts.  The purpose of this paper is to present an analysis of the use of Geographic Information Systems (GIS) as a tool for the PMS, as a first attempt, in Amman-Jordan.